2007
DOI: 10.1111/j.1365-2362.2007.01808.x
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related changes in bile acid synthesis and hepatic nuclear receptor expression

Abstract: Ageing associates with reduced bile acid synthesis, possibly related to decreased hepatic expression of hepatocyte nuclear factor-4 and consequently of cholesterol 7alpha-hydroxylase. Age-related modifications of the growth hormone/insulin-like growth factor axis might play a role. These findings may help to elucidate the pathophysiology of age-related modifications of cholesterol metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 47 publications
4
40
1
1
Order By: Relevance
“…A decline in bile acid synthesis and hepatic expression of CYP7A1 have been shown to be correlated with ageing in human subjects (Bertolotti et al, 2007). This decreases cholesterol utilisation for the de novo synthesis of bile acids (Bertolotti et al, 2007). This is supported by Bertolotti et al (1993) who carried out a linear regression analysis which estimated that the amount of cholesterol undergoing the CYP7A1 regulated reaction in humans decreases by 60mg per day, every 10 years (Bertolotti et al, 1993).…”
Section: How Cholesterol Metabolism Changes With Agementioning
confidence: 96%
See 2 more Smart Citations
“…A decline in bile acid synthesis and hepatic expression of CYP7A1 have been shown to be correlated with ageing in human subjects (Bertolotti et al, 2007). This decreases cholesterol utilisation for the de novo synthesis of bile acids (Bertolotti et al, 2007). This is supported by Bertolotti et al (1993) who carried out a linear regression analysis which estimated that the amount of cholesterol undergoing the CYP7A1 regulated reaction in humans decreases by 60mg per day, every 10 years (Bertolotti et al, 1993).…”
Section: How Cholesterol Metabolism Changes With Agementioning
confidence: 96%
“…Additionally, this could be due to the decreased demand for cholesterol for the de novo synthesis of bile acid, due to the age-related decrease in bile acid synthesis (Ericsson et al, 1991). A decline in bile acid synthesis and hepatic expression of CYP7A1 have been shown to be correlated with ageing in human subjects (Bertolotti et al, 2007). This decreases cholesterol utilisation for the de novo synthesis of bile acids (Bertolotti et al, 2007).…”
Section: How Cholesterol Metabolism Changes With Agementioning
confidence: 99%
See 1 more Smart Citation
“…Bertolotti et al (63) estimated by linear regression analysis a 60 mg/d (about 150 µM/ d) decline every 10 years, in cholesterol undergoing cholesterol 7α-hydroxylation, while Einarsson et al (64) estimated an 80 mg/d (200 µM/d) reduction over the same time period. Bertolotti et al (62) propose the age-related reduction in CYP7A1 expression could be related to the concomitant decline in hepatic nuclear factor four and co-activator CYP7A1 promoter-binding factor/liver receptor homologue-1, mediated by the decline in growth hormone and insulin-like growth factor.…”
Section: Intrinsic Ageingmentioning
confidence: 99%
“…Consequently, the data are inconsistent [13,14]. Bertolotti et al [15] recently found a negative correlation between age and serum C4 concentrations and also with age and hepatic cholesterol 7a-hydroxylase m-RNA expression.…”
Section: Introductionmentioning
confidence: 99%